Exemplary online information literacy courses at selected four-year colleges and universities - Creed-Dikeogu, Gloria (Kansas State University, 2017)
Twenty three in-depth qualitative telephone interviews were conducted in this multiple case study with instruction librarians at eight four-year colleges and universities. Snowball sampling was used to select instruction librarian, information literacy department head and administration participants employed at institutions recognized by Association of College and Research Libraries for exemplary information literacy best practices: information programs. The questions researched in this dissertation were: How are selected four-year colleges implementing exemplary information literacy courses? How do exemplary four-year college library information literacy courses implement the Association of College and Research Libraries Framework for Information Literacy in Higher Education (2016)? How do exemplary four-year colleges and universities implement digital literacy and the six frames of the Association of College and Research Libraries Framework for Information Literacy for Higher Education (2016)? The Association of College and Research Libraries Standards (2000) and the Framework for information literacy for higher education (2016) were used as a foundation for this study. A conceptual framework was built in this study around information literacy historical underpinnings and five major national educational reports that were submitted to Congress between 1983 and 1989. These reports accelerated the information literacy agenda in institutions. The major study findings suggested that information literacy programs in institutions were most successful when the library’s program was supported by the institution’s administration. Successful information literacy course and program implementation in all eight institutional settings were dependent on the collaborative arrangements made between the instructional librarians and the faculty. Online information literacy courses were not common at the eight institutions. Information literacy instruction was blended and information literacy tutorials provided to students had online-components. Instruction librarians were using best practices in six areas that directly related to the development and design of the information literacy course: in their reference interactions with students, in choosing information literacy and teaching and learning models that would fit their institution’s programs, in the development of information literacy curriculum, in curriculum and program administration procedures and in assessing their information literacy courses and programs. Findings also indicated that although there was a great deal of anecdotal evidence that instructors provided that their students were information literate when they graduated, and that they were lifelong learners, no institutions had implemented tests for seniors that determined whether they were graduating information literate.
Keywords: Blended learning; Curriculum and instruction; Online learning; Instruction--information literacyInformation Literacy